Being an Elderly Person Living in Metropolitan Cities of Northwestern Ethiopia: A Descriptive Phenomenological Study - Mekonnen HS; Lindgren H; Geda B; Azale T; Erlandsson K (Clinical Interventions in Aging, 2023)
Habtamu Sewunet Mekonnen,1 Helena Lindgren,2 Biftu Geda,3 Telake Azale,4 Kerstin Erlandsson5 1Department of Medical Nursing, School of Nursing, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Women’s and Children’s Health, Karolinska Institutet, Solna, Sweden; 3Department of Nursing, College of Health Science, Madda Walabu University, Shashemene Campus, Shashemene, Ethiopia; 4Department of Health Education and Behavioral Sciences, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 5Department of Women’s and Children’s Health, Karolinska Institutet, Solna, Sweden and School of Education, Health and Social Studies, Dalarna University, Falun, SwedenCorrespondence: Habtamu Sewunet Mekonnen, Email habtsew@ymail.comBackground: As people grow old, they pass through various life courses. Thus, it is important to realize aging in the context of each of these stages, as aging is not only physiological and psychological processes. To understand the lifeworld experiences of the phenomenon “being an elderly person” from the individual perspective was important, in this study, within day-to-day life in Metropolitan cities of northwestern Ethiopia.Objective: The aim of this study was to describe the lifeworld of elderly persons living in Bahir Dar and Gondar Cities, Northwest Ethiopia.Methods: A community based qualitative study conducted from October 29, 2021 to November 6, 2021. A purposive sampling technique and in-depth interviews were used for sampling and data collection, respectively. To explore the life experience /life-world/ of the elderly, a descriptive phenomenological study was conducted among 15 elderly persons. The audio records were transcribed and the field notes incorporated. Transcribed texts were translated into the English language, and a descriptive phenomenological analysis was done.Results: In this study, the essence of the phenomenon, being an elderly person, means, in an ebb and flow motion, balancing a life change characterized by changing perspective, ambiguity to body functions, and preparing for being released. The elderly experienced physical, mental, and psychosocial changes. They had encountered positive and negative situations throughout their life span. They also expressed that their time was over and wished to prepare for God’s Kingdom.Conclusion: The use of phenomenology for this research provided an opportunity for a deeper understanding of the experiences of elderly persons. With knowledge from this study, nurses and other health professionals can understand and support the elderly from an individual point of view.Keywords: elderly person, Ethiopia, lifeworld, phenomenology